Loans, logins and lasting the course: Academic library use and student retention - Haddow, Gaby; Joseph, Jayanthi (Australian Library and Information Association, 2010)
Activities and services that improve student engagement and retention in the higher education sector are important not only to individual student’s success but also to university planning and funding. This paper reports on a quantitative study that was carried out to explore whether use of the library by new university students is associated with continued enrolment. Students’ socioeconomic background and age were also examined in relation to library use. Limited to commencing students in March 2010 at Curtin University, the study drew on demographic data from the University’s enrolment system and instances of library use from the Library’s management system. Results of the statistical analyses indicate that library use is associated with retention, and importantly, library use in the early weeks of a student’s first semester is associated with retention. ‘Mature aged’ (21 years and over) students displayed different library use patterns than their younger colleagues and there was some variation in library use between students from different socioeconomic backgrounds. Findings from this study suggest that academic libraries can contribute to the retention of students and that carefully targeted programs and services may improve library use by some groups of students.